Generalised geometry and flux vacua: A very short review. Issue 4 (9th March 2016) - Larfors, Magdalena
Abstract : This note discusses the connection between generalised geometry and flux compactifications of string theory. Firstly, we explain in a pedestrian manner how the supersymmetry constraints of type II flux compactifications can be restated as integrability constraints on certain generalised complex structures. This reformulation uses generalised complex geometry, a mathematical framework that geometrizes the B‐field. Secondly, we discuss how exceptional generalised geometry may provide a similar geometrization of the RR fields. Thirdly, we examine the connection between generalised geometry and non‐geometry, and finally we present recent developments where generalised geometry is used to construct explicit examples of flux compactifications to flat space.